Criminal Law Reform Policy in Indonesia: Balancing Justice, Morality, and Human Rights - Mulyana, H. Yusep (Ipso Jure, 2025)
Criminal law reform in Indonesia is not only a legislative process, but also a reflection of complex battles over values and political interests. This study aims to analyze the role of political law in shaping the balance between justice, morality, and human rights in the 2023 revision of the Criminal Code (KUHP). Using a qualitative approach through document analysis, case studies, and interviews with legal experts and human rights activists, this study finds that politics plays a dominant role in determining the direction of criminal law reform. The tug-of-war between conservative and progressive groups creates legal compromises that often blur the line between social morality and the protection of human rights. The results of the study show that criminal law in Indonesia still functions as an instrument of political legitimacy, not merely as a means of substantive justice. Therefore, a participatory and transparent approach is needed so that criminal law reform can uphold social justice without sacrificing the basic rights of citizens.